The DISTANCE study: Determining the impact of social distancing on trauma epidemiology during the COVID-19 epidemic—An interrupted time-series analysis. Issue 4 (5th April 2021) - Matthay, Zachary A.; Kornblith, Aaron E.; Matthay, Ellicott C.; Sedaghati, Mahsa; Peterson, Sue; Boeck, Marissa; Bongiovanni, Tasce; Campbell, Andre; Chalwell, Lauren; Colwell, Christopher; Farrell, Michael S.; Kim, Woon Cho; et al.
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: The large-scale social distancing efforts to reduce SARS-CoV-2 transmission have dramatically changed human behaviors associated with traumatic injuries. Trauma centers have reported decreases in trauma volume, paralleled by changes in injury mechanisms. We aimed to quantify changes in trauma epidemiology at an urban Level I trauma center in a county that instituted one of the earliest shelter-in-place orders to inform trauma care during future pandemic responses. METHODS: A single-center interrupted time-series analysis was performed to identify associations of shelter-in-place with trauma volume, injury mechanisms, and patient demographics in San Francisco, California. To control for short-term trends in trauma epidemiology, weekly level data were analyzed 6 months before shelter-in-place. To control for long-term trends, monthly level data were analyzed 5 years before shelter-in-place. RESULTS: Trauma volume decreased by 50% in the week following shelter-in-place ( p < 0.01), followed by a linear increase each successive week ( p < 0.01). Despite this, trauma volume for each month (March–June 2020) remained lower compared with corresponding months for all previous 5 years (2015–2019). Pediatric trauma volume showed similar trends with initial decreases ( p = 0.02) followed by steady increases ( p = 0.05). Reductions in trauma volumes were due entirely to changes in nonviolent injury mechanisms, while violence-related injury mechanisms remained unchanged ( p < 0.01). CONCLUSION: Although the shelter-in-place order was associated with an overall decline in trauma volume, violence-related injuries persisted. Delineating and addressing underlying factors driving persistent violence-related injuries during shelter-in-place orders should be a focus of public health efforts in preparation for future pandemic responses. LEVEL OF EVIDENCE: Epidemiological study, level III.